Urban housing and slums - Jain, A. K. (New Delhi : Readworthy Publications, 2009)
With reference to India.
Includes index.
Includes statistical tables.
Keywords: Urban poor -- Housing; Housing policy; Slums -- Government policy; Squatter settlements -- Government policy